Hutang Sebagai Penopang Gaya Hidup Buruh Perempuan di Desa Sugihwaras - Sa’adah, Miftahus (Paradigma, 2022)
Debt is something that is often experienced by female workers in Sugihwaras village. Women workers take advantage of debt to support their lifestyle, which cannot be fulfilled due to low economic conditions. The purpose of this study was to find out how debt is used to support the lifestyle of female workers in Sugihwaras village. David Chaney’s lifestyle theory is used to analyze the results of this study. The research method used is qualitative with hiles and huberman concept data analysis techniques. The results showed that female workers have a consumptive lifestyle, seen from their activities, interests and opinions. They always follow trends, spend their free time for entertainment and are consumptive in spending their money. The purpose of women workers maintaining this lifestyle is to give the best impression on themselves (self-image), show a higher social status than others (social identity) and be accepted by their social group (social adjustment). Keywords: lifestyle, female labor, debt.